GRAMMATICAL ERRORS IN WRITING UNDERGRADUATE THESIS PROPOSAL: A STUDY CASE ON THE LAST SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM OF NUSA CENDANA UNIVERSITY IN THE ACADEMIC YEAR 2020-2021 - Elisna Huan; John Wem Haan; Dewi I. N. Bili Bora; Sebastianus Fernandez; Laurensius Kian Bera (Academic Journal of Educational Sciences, 2021)
Research with topics like this is not new, educators usually try to find out the weaknesses of their students in terms of mastery of grammar to solve the teaching and learning problems. English study Program of FKIP, Universitas Nusa Cendana also see this as something urgent so it is very necessary to do to see and identify the weaknesses of students English Education study program in writing scientific papers (thesis) from the grammatical point of view by using the surface strategy taxonomy approach introduced by Dulay, Burt, and Krashen (1982). This research is expected to contribute to the teaching and learning process in the study program, especially for several related subjects such as Writing I, II, III, and Academic Writing. By identifying students’ problems in writing thesis proposals, educators, especially lecturers of the English Education Study Program are expected to be able to map the problems of English study program students and make them a reference for teaching.